Analisis Dampak Hemoroid pada Kehamilan - Hanang Novianto; Erma Rachmayanti (LPPM Institut Nasional Laa Roiba Bogor, 2023)
Hemorrhoids during pregnancy is one of the problems that pregnant women often complain about. It is estimated that around 25-35 percent of pregnant women experience this condition, also known as hemorrhoids. Hemorrhoids during pregnancy usually begin to appear at week 25 or in the last trimester of pregnancy. Hemorrhoids in pregnant women are a physiological condition, so the therapy is aimed at overcoming complaints, namely with preventive measures and animation. New surgery is performed if the animation treatment is not successful. Keywords: Hemorroid, Pregnancy